Looking into my body - Nigel, Nelson (Joshua Morris Publishing, Inc, 1996)
Looking Into. . . My Body features simple, scientifically correct illustrations on specially designed "see;-through" windows that reveal tha amazing workings of the human body.
Keywords: Body-Juvenile literature